The Influence of Halal Business Legality and Product Packaging on Purchasing Decisions at Umkm Chips Partner House Bumn Bandar Lampung - Aina Haliza; M. Oktaviannur (Cita konsultindo, 2024)
This study aims to investigate the effect of halal business legality as well as product packaging on purchasing decisions at MSMEs in the field of chips, with a focus on BUMN House Partners in Bandar Lampung. In the era of increasingly fierce business competition, aspects of product halalness and packaging design play an important role in shaping consumer perceptions and influencing purchasing decisions. Quantitative research methods are used by collecting data through questionnaires distributed to consumers of BUMN Home Partners who buy chips. The data collected was then analyzed using regression techniques to test the effect of halal business legality variables and product packaging on purchasing decisions. The result of this study is that there is a significant influence between halal business legality and product packaging for purchasing decisions. The implications of the results of this study are expected to help SOE House Partners and similar MSMEs in optimizing their marketing strategies, improving brand image, and accessing markets more effectively. Keywords: Halal Business Legality; Product Packaging; Purchasing Decisions